Pengaruh Pemanfaatan Sistem Informasi SI INTAN DARA dan Kompetensi SDM terhadap Peningkatan PAD Kabupaten Banjar - Siti Fatimah; Pipit Angelia Widiarti; Akhmad Maulana (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
The purpose of this study is to analyze the effect of the utilization of the Regional Revenue Service Information System Application (SI INTAN DARA) and human resource competence on the improvement of Regional Original Revenue at the Regional Financial,Revenue, and Asset Management Agency of Banjar Regency,both simultaneously and partially, and to determine the most dominant influencing variable. The research method used is a quantitative approach with an associative research design. The population ofthis study consists ofall 120employees of the Regional Financial,Revenue, and Asset Management Agency of Banjar Regency, with the sampling technique using a census method (total sampling).Data were collected through questionnaires that had been testedl for validity and reliability and were analyzed using multiple linear regression analysis.Hypothesis testing was conducted using simultaneous tests (F-test), partial tests (t-test), and ddominance tests. The results show that the utilization of the SI INTAN DARA application and human resource competence have a positive and significant effect simultaneously on the improvement of Regional Original Revenue. Partially, both variables also have a positive and significant effect. The most dominant variable influencing the improvement of Regional Original Revenue is the utilization of the SI INTAN DARA application.